2018
DOI: 10.1007/s00467-018-3933-3
|View full text |Cite
|
Sign up to set email alerts
|

Extra-Renal manifestations of atypical hemolytic uremic syndrome in children

Abstract: The most common and serious extrarenal manifestation of aHUS is neurological involvement and treatment outcome findings presented herein are important to all relevant clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 31 publications
1
28
0
8
Order By: Relevance
“…aHUS is a rare disease that belongs to the TMA spectrum 1 and is characterized by a triad of microangiopathic hemolytic anemia with direct negative Coombs, thrombocytopenia, and acute renal injury. It is secondary to uncontrolled activation of the alternate pathway of the complement cascade due to genetic defects, which can be identified in more than 50% of cases [2][3][4] . Its differential diagnosis includes thrombotic thrombocytopenic purpura (TTP) due to deficiency in ADAMTS13 enzyme activity; hemolytic uremic syndrome associated with Shiga-toxin-producing bacteria (typical SHU), and secondary TMA 1,3,5,6 .…”
Section: Clinical Casementioning
confidence: 99%
“…aHUS is a rare disease that belongs to the TMA spectrum 1 and is characterized by a triad of microangiopathic hemolytic anemia with direct negative Coombs, thrombocytopenia, and acute renal injury. It is secondary to uncontrolled activation of the alternate pathway of the complement cascade due to genetic defects, which can be identified in more than 50% of cases [2][3][4] . Its differential diagnosis includes thrombotic thrombocytopenic purpura (TTP) due to deficiency in ADAMTS13 enzyme activity; hemolytic uremic syndrome associated with Shiga-toxin-producing bacteria (typical SHU), and secondary TMA 1,3,5,6 .…”
Section: Clinical Casementioning
confidence: 99%
“…The present case showed CNS involvement, including a headache, seizure, and visual disorders, which are extremely common in aHUS patients (16). In a Turkish registry of pediatric aHUS patients, seizure and visual loss were observed in 20.7% and 2.3% of patients, respectively (17). Magnetic resonance imaging of the brain revealed posterior reversible encephalopathy syndrome, which is sometimes observed in aHUS patients (17).…”
Section: Discussionmentioning
confidence: 49%
“…In a Turkish registry of pediatric aHUS patients, seizure and visual loss were observed in 20.7% and 2.3% of patients, respectively (17). Magnetic resonance imaging of the brain revealed posterior reversible encephalopathy syndrome, which is sometimes observed in aHUS patients (17). The patient also presented with gastrointestinal disorders including abdominal pain and diarrhea, which are commonly involved in aHUS (16).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies did not emphasize the prognostic importance of tubular atrophy and interstitial fibrosis in this disease. 5,9,11,12,14,1921,23,24 However, we observed that particularly any degree of interstitial fibrosis was associated with more severe presentation and worse prognosis. It is well known that a positive correlation exists between deteriorated renal functions and chronic changes in the interstitial compartment irrespective of the underlying renal disease.…”
Section: Discussionmentioning
confidence: 51%
“…5,6 Clinicians agree that severe initial presentation, persistent oliguria or anuria, need for dialysis, and central nervous system involvement are indicators of a poor prognosis. 79 However, the relationship between initial histopathological findings and clinical features at presentation and long-term outcomes in children with aHUS is not definitely known. 10,11…”
Section: Introductionmentioning
confidence: 99%